2023
DOI: 10.3389/fspor.2023.1258542
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of supplement use and knowledge among Japanese elite athletes for the Tokyo 2020 Olympic/Paralympic games and the Beijing 2022 winter Olympic/Paralympic games

Kanae Myoenzono,
Jun Yasuda,
Eri Takai
et al.

Abstract: Elite athletes frequently invest in the use of supplements to optimize their dietary regimens and enhance their athletic performance. However, unregulated and unplanned use of supplements can lead to adverse consequences, including anti-doping rule violations or health issues. Thus, athletes should verify their diets, consider scientific evidence, and take necessary precautions regarding supplements before use. To date, no study has explored whether athletes check these factors before using supplements. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
3
1
Order By: Relevance
“…The next strongest impact on the algorithm was based on athletes not searching for information before using a supplement. In the current study, one-fifth of the athletes reported not to search for information on their own, which was substantially lower than earlier reported, as 50% of Japanese elite Olympic athletes reported not reviewing scientific evidence before using nutritional supplements ( 30 ). Two other predictors, both contributing with a similar weight to the algorithm, where purchasing supplements outside of what the athletic department provides, as well as taking advice from non-experts, increased the chance of inconsistent TPT use.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…The next strongest impact on the algorithm was based on athletes not searching for information before using a supplement. In the current study, one-fifth of the athletes reported not to search for information on their own, which was substantially lower than earlier reported, as 50% of Japanese elite Olympic athletes reported not reviewing scientific evidence before using nutritional supplements ( 30 ). Two other predictors, both contributing with a similar weight to the algorithm, where purchasing supplements outside of what the athletic department provides, as well as taking advice from non-experts, increased the chance of inconsistent TPT use.…”
Section: Discussioncontrasting
confidence: 77%
“…Almost two-thirds of the athletes discussed supplement choices with their registered dietitian, which was the fourth predictive variable, being associated with a lower risk of not using TPT supplements. This can be related with better informed choices by athletes when counseled by a dietitian ( 16 ), while in reality athletes also report lower percentages for consulting a dietitian related to supplement use, ranging in other recent publications from 25% ( 33 ) to 50% ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In competition and exercise training, dietary supplement use is widespread and common among elite athletes (e.g., Japanese Olympic and Paralympic athletes [ 5 ], Spanish elite male and female athletes [ 6 ], gym members [ 7 ], recreationally active students [ 8 ], and ultramarathoners [ 9 ]). In addition, many position statements have provided evidence for the ergogenic nutritional potential of dietary supplements and nutritional considerations in different cohorts (e.g., [ 10 , 11 ]), including for single-stage ultra-endurance events [ 12 ].…”
Section: Introductionmentioning
confidence: 99%